An ethnobotanical survey of medicinal plants used for children’s healthcare in Centre-Est Burkina Faso - Antognoni, Fabiana; Nadembega, Pascal; Zongo, Luc; Afifi, Sherif M; Lianza, Mariacaterina; Currier, Alain (Ethnobotany Research and Applications, 2026)
Background: In Burkina Faso, a large part of population cannot afford conventional medicines, making the plant-based traditional ones essential for healthcare. Despite recent government efforts to ensure children's right to health, the under-five mortality rate remains high. The objective of this study is to establish a comprehensive database of plants commonly used by traditional healers in childhood disease management. Methods: The survey was conducted in Centre-Est Burkina Faso between May 2019 and October 2023 using open and semi-structured interviews with 43 informants including paediatric traditional healers (22), herb vendors (15), and children’s mothers and relatives (6). Ethnobotanical data were analyzed using informant consensus factor and fidelity level (FL). Results: The study documented 185 species from 52 plant families. High informant consensus factor (0.82-0.93) indicates a strong agreement among healers about the therapeutic use of medicinal plants, with malaria being the most frequently treated disease (111 species cited for it). Vitellaria paradoxa C.f. Gaertn emerged as the most used species with 100% FL, and Fabaceae (19.2%), Malvaceae (8.6%), Poaceae (8.3%), Rubiaceae (4.7%) and Combretaceae (4.2%) were the most represented families. Conclusions: This ethnobotanical survey is one of the most important studies in Centre-Est Burkina Faso on medicinal plants paving the way for the management of most frequent childhood’s diseases. The findings confirm the widespread use of plants in paediatric healthcare and emphasize the key role of traditional healers, particularly women, in local communities. The survey contributes to safeguarding regional medicinal biodiversity and provides a basis for future phytochemical investigations. Keywords: African traditional medicine, biodiversity, practitioners, pediatric healthcare, traditional healers.